2016
DOI: 10.1166/jnn.2016.12839
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Transparent Conducting Oxide Nanomaterials; Aluminium- and Gallium-Co-Doped Zinc Oxide (AGZO)

Abstract: Transparent conducting oxide (TCO) nanoparticles based on zinc oxide doped with aluminium and gallium (Al-and Ga-co-doped ZnO, AGZO) were synthesized using a continuous hydrothermal flow synthesis (CHFS) reactor by rapid hydrolysis and dehydration of aqueous metal salt precursors, in the presence of formic acid as an in-process reducing agent. The as-synthesised powders were characterized by powder X-ray diffraction (pXRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In 2011 the RAMSI process was decommissioned to make way for a higher throughput manual HiTCH process that allowed more flexible sample sizes. ,, Metal salt mixing in the UCL authors laboratory is now conducted by a liquid handler, which offers significant time savings and better accuracy than a person doing such tasks. For example, a HiTCH-type approach was used to make libraries of Li-ion cathode materials based on LiMn 1– x – y Fe x V y PO 4 …”
Section: Miscellaneous Nanomaterials’ Chemistry and Process Developmentsmentioning
confidence: 99%
“…In 2011 the RAMSI process was decommissioned to make way for a higher throughput manual HiTCH process that allowed more flexible sample sizes. ,, Metal salt mixing in the UCL authors laboratory is now conducted by a liquid handler, which offers significant time savings and better accuracy than a person doing such tasks. For example, a HiTCH-type approach was used to make libraries of Li-ion cathode materials based on LiMn 1– x – y Fe x V y PO 4 …”
Section: Miscellaneous Nanomaterials’ Chemistry and Process Developmentsmentioning
confidence: 99%
“…Both the optimum resistivity of AZO and that of GZO reported herein, are a signicant improvement on the value of 4.6 Â 10 À2 U cm, as reported by the authors elsewhere for the corresponding co-doped system. 36 Pilot scale continuous hydrothermal synthesis of AZO and GZO Whilst the scale of the synthesis discussed thus far (rate of 60 g per hour) was suitable for high-throughput synthesis and screening of doped zinc oxide nanomaterials, production of such materials at still larger scales is critical for practical industrial applications. Previous reports by the authors have demonstrated the scale-up of the CHFS process for the synthesis of ZnO 27 and Ce-Zn oxide nanoparticles 29 in a continuous supercritical water pilot plant.…”
Section: High-throughput Screening Of Azo and Gzo Nanomaterialsmentioning
confidence: 99%
“…31 The authors have also investigated the CHFS synthesis of co-doped zinc oxide (with both Al and Ga and known as AGZO) using formic acid as an in-process reducing agent, which gave a resistivity of 4.6 Â 10 À2 U cm. 36 Herein, we report the rst CHFS synthesis of highly conductive optimised AZO and GZO nanoparticles followed by heat-treatment in reducing conditions. Compositional space for each doped system was rst explored (up to 6 at%) using a labscale CHFS reactor at a production rate of 60 g per hour.…”
Section: Introductionmentioning
confidence: 99%
“…These compositions demonstrated electrical properties matching those found for optimal GZO samples synthesized and tested by the same methods, offering reduced cost compared to GZO samples (due to the introduction of aluminum to partially replace the gallium present in the structure). These values are almost an order of magnitude lower than the previously best reported resistivities of AGZO materials synthesized by CHFS-type processes . The carrier concentrations in these highly conductive samples were 1.9 × 10 19 , 6.3 × 10 18 , and 6.5 × 10 18 cm –3 for A 3.0 G 1.0 ZO, A 2.0 G 2.0 ZO, and A 1.0 G 2.0 ZO, respectively, while the carrier mobilities were 365, 139, and 122 cm 2 V –1 s –1 , respectively, showing considerably more variability than the resistivities.…”
Section: Resultsmentioning
confidence: 58%
“…These values are almost an order of magnitude lower than the previously best reported resistivities of AGZO materials synthesized by CHFS-type processes. 68 The carrier concentrations in these highly conductive samples were 1.9 x 10 19 cm -3 , 6.3 x 10 18 cm -3 , and 6.5 x 10 18 cm -3 for A3.0G1.0ZO, A2.0G2.0ZO, and A1.0G2.0ZO, respectively, while the carrier mobilities were 365 cm 2 V -1 s -1 , 139 cm 2 V -1 s -1 , and 122 cm 2 V -1 s -1 , respectively, showing considerably more variability than the resistivities. Thus, the composition of A3.0G1.0ZO was found to be optimal with respect to electrical properties, showing both the highest measured mobility and charge carrier density.…”
Section: Electrical Characterizationmentioning
confidence: 99%